Antibiotics and Probiotics Prophylaxis for Recurrent Urinary Tract Infection in Children - Jung Won Lee (Korean Society of Pediatric Nephrology, 2016)
Since many years, continuous low dose antibiotic prophylaxis (CAP) has been used for children at a risk for recurrent urinary tract infection (UTI), especially those with vesicoureteral reflux (VUR). The incidence of recurrent UTI has been shown to be higher in children with VUR with bladder and bowel dysfunction (BBD) than in those with VUR without BBD. Therefore, CAP has been recommended for children with BBD and VUR because of the increased risk of UTI. However, the use of CAP has become highly controversial because of bacterial resistance developed due to antibiotic over-usage. The preventive effects of probiotics have been proved in various adult urogenital infections, and the antimicrobial activities of lactobacilli against uropathogens have been demonstrated in previous in vitro studies. However, a critical assessment of their efficacy in children with UTI is lacking. The importance of the use of urogenital probiotics is that it is a natural approach that replenishes the depleted normal flora to create a better environment to fight off uropathogens. Probiotics have a great potential, particularly today with the increasing threat of antibiotic-resistant microorganisms.